2012
DOI: 10.1145/2366145.2366220
|View full text |Cite
|
Sign up to set email alerts
|

Calibrated image appearance reproduction

Abstract: Managing the appearance of images across different display environments is a difficult problem, exacerbated by the proliferation of high dynamic range imaging technologies. Tone reproduction is often limited to luminance adjustment and is rarely calibrated against psychophysical data, while color appearance modeling addresses color reproduction in a calibrated manner, albeit over a limited luminance range. Only a few image appearance models bridge the gap, borrowing ideas from both areas. Our take on scene rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…bright for outdoor displays, dim for cinema) [Reinhard et al 2012]. HDR is then defined as a large range of displayable luminance values above and below this adaptation level, typically several orders of magnitude wide.…”
Section: Technical Approach and Resultsmentioning
confidence: 99%
“…bright for outdoor displays, dim for cinema) [Reinhard et al 2012]. HDR is then defined as a large range of displayable luminance values above and below this adaptation level, typically several orders of magnitude wide.…”
Section: Technical Approach and Resultsmentioning
confidence: 99%
“…Another approach is to aim at minimizing the changes in contrasts, given that the dynamic range is compressed to a certain display device [77,170]. Other SRP goals include, for example, preservation of visibility [264], perceived lightness [133], color appearance [138,212], and temporal consistency [38,107].…”
Section: Scene Reproduction (Srp) Operatormentioning
confidence: 99%
“…For example, there are examples of methods that perform the compression in the gradient [89,148,254] or contrast [167] domain. Also, a number of methods attempt to model the appearance of colors [6,86,129,138,198,212]. However, the most common method is to only consider luminance, and restore colors after this has been compressed [220].…”
Section: Pre-processingmentioning
confidence: 99%
“…In contrast to the operators discussed so far, CAMs process each channel of the image separately rather than only compress luminance [26]. Typically, such models employ both a forward and an inverse step, taking the scene and viewing parameters into account, although it was recently shown that the inverse step may be bypassed, while still accurately reproducing color appearance [27]. …”
Section: Color Management In Tone Reproductionmentioning
confidence: 99%